The “Oyun tülkigür” or “Key to Wisdom” and Statement of Emotional Intelligence - Otgonbayar, Ankhiluun; Dashdamba, Erdenesan (Mongolian Language and Literature Studies, 2025)
This article explores the interdisciplinary concept of Emotional Intelligence, which has been studied in the West since the 19th century across the fields of psychology, neuroscience, sociology, and education. We hypothesize that elements of emotional intelligence may be implicitly present in the Mongolian written heritage-specifically, in the wisdom literature The Key to Wisdom (Oyun tülkigür), a traditional moral teaching. To examine this, we compared three manuscript versions of the text with the published version included in Academician Ts. Damdinsuren’s compilation “mongγul-un uran ĵokiyal-un degeji ĵaγun bilig orusibai” (A Hundred Treasured Works of Mongolian Literature). We further analyzed the content in relation to the four core domains of emotional intelligence: perceiving, using, understanding, and managing emotions-each of which includes a set of 26 distinct skills. Based on our findings, we propose that Mongolian traditional pedagogical philosophy can be revisited through the lens of contemporary scientific understanding and suggest its potential integration into modern educational frameworks, particularly within the curricula of “Civic Ethics Education” and “Human and Society” subjects. Оюуныг нээгч “Оюун түлхүүр” сургаал хийгээд сэтгэл хөдлөлийн оюун ухаан (EI)-ы өгүүлэмж Хураангуй: Тус өгүүлэлд сэтгэл судлал, тархи судлал, социологи, боловсролын буюу салбар дундын шинжтэй, Өрнө дахинаа XIX зуунаас судлагдаж эхэлсэн “Сэтгэл хөдлөлийн оюун ухаан” (Emotional Intelligence) нь Монголын бичгийн дурсгал болох оюуныг нээгч “Оюун түлхүүр” сургаалын зохиолд өгүүлэгдсэн байх магадлалыг таамаглаж, тус зохиолын гурван гар бичмэлийг академич Ц.Дамдинсүрэнгийн “Монголын уран зохиолын дээж зуун билиг оршвой” бүтээлд хэвлүүлсэн хувилбартай харьцуулан ажиглаж, цаашлаад сэтгэл хөдлөлийн оюун ухааны таних, хэрэглэх, ойлгох, удирдах гэсэн дөрвөн түвшний 26 чадвартай харгалзуулан шинжлэв. Эндээс монголын уламжлалт сурган хүмүүжүүлэх ухааныг орчин үеийн шинжлэх ухааны үүднээс авч үзэн, өнөөгийн боловсролын үзэл баримтлал, түүн дотор “Иргэний ёс зүйн боловсрол” ба “Хүн нийгэм” гэсэн 2 хичээлийн хөтөлбөрт тусган интеграцчилж ашиглах боломжтой гэсэн санал дэвшүүлэв. Түлхүүр үгс: Сургаалын зохиол, эх судлал, “Оюун түлхүүр” сургаал, сэтгэл хөдлөлийн оюун ухаан